2009
DOI: 10.1093/rheumatology/kep381
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal manifestation of systemic sclerosis—thickening of the upper gastrointestinal wall detected by endoscopic ultrasound is a valid sign

Abstract: Objective. Gastrointestinal (GI) tract involvement has been observed in the majority of patients with SSc. This has been attributed to an accumulation of extracellular matrix within the GI walls. We visualized the walls of the oesophagus, stomach and duodenum with its layers and measured the thickness in SSc patients and control patients utilizing endoscopic ultrasound (EUS).Methods. Twenty-five SSc patients and 25 controls were evaluated. In addition to analysis of clinical symptoms, endoscopy and EUS (20-MHz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…Dermal skin thickness, which is caused by increased collagen deposition, is thought to correlate with more severe internal organ involvement, morbidity, and mortality . A study utilizing endoscopic ultrasound identified thickened (compared with normal controls) esophageal walls, mainly in the submucosa and muscularis, in 14 patients with dcSSc and 11 lcSSc, which also correlated with the presence of dysphagia . Prior studies report variable associations between esophageal dysfunction and esophageal symptoms in patients with SSc, including reports of asymptomatic individuals with severe esophageal disease .…”
Section: Discussionmentioning
confidence: 99%
“…Dermal skin thickness, which is caused by increased collagen deposition, is thought to correlate with more severe internal organ involvement, morbidity, and mortality . A study utilizing endoscopic ultrasound identified thickened (compared with normal controls) esophageal walls, mainly in the submucosa and muscularis, in 14 patients with dcSSc and 11 lcSSc, which also correlated with the presence of dysphagia . Prior studies report variable associations between esophageal dysfunction and esophageal symptoms in patients with SSc, including reports of asymptomatic individuals with severe esophageal disease .…”
Section: Discussionmentioning
confidence: 99%
“…1), which is intimately attached to the head and would facilitate luminal sparing due to the thinner thickness of the duodenal wall (2 mm distended) as compared to the stomach wall (3-5 mm) in humans. [33][34][35] In the porcine model, the head of the pancreas (the duodenal lobe) is the smallest volumetric portion of the pancreas 36 and is separated from the medial duodenum by mesentery, leaving potential gaps between the two organs. 37 Further, the pyloric region that connects the stomach and duodenum contains a mucosal protuberance called the torus pyloricus, which results in much more constriction in the porcine model than in humans, impeding endoluminal access.…”
Section: Discussionmentioning
confidence: 99%
“…Localized cooling effects of major blood vessels were modeled using heat flux boundary conditions at the inner surface of the blood vessels, with an ambient blood temperature of 37 °C, and the heat transfer coefficient h value was calculated using the method detailed by Haemmerich et al, with vasculature parameters obtained from literature [5560]. The duodenal and stomach walls were modeled as 2 mm and 3 mm thick, respectively [53,61,62]. Feedback control over the maximum tumor temperature was applied for the ablation simulations and transient temperature solutions were obtained.…”
Section: Methodsmentioning
confidence: 99%